Exploring the usefulness of the complex in vitro intestinal epithelial model Caco-2/HT29/Raji-B in nanotoxicology. (March 2018) - García-Rodríguez, Alba; Vila, Laura; Cortés, Constanza; Hernández, Alba; Marcos, Ricard
Abstract: The use of in vitro barrier models is gaining relevance as an alternative to animal studies in risk assessment, pharmacokinetic, and toxicological studies in general. These models permit an easier evaluation of the underlying mechanisms taking place at the molecular and cellular levels on the barrier site. Here, we report several methodological modifications of the three-dimensional in vitro intestinal epithelial model Caco-2/HT29/Raji-B for its successful application in the Nanotoxicology field. In addition, new insights in the study of specific molecular markers and new confocal microscope approaches have also been incorporated. Due to the multiple variables and parameters playing a part when the model's complexity is increased, we have monitored the barrier's formation and cell differentiation over time. Finally, the practical usability of the proposed model was tested by evaluating the action of the food additives titanium dioxide and silica dioxide nanoparticles (TiO2 NPs and SiO2 NPs). The NPs-associated effects were evaluated by confocal microscopy. We have demonstrated the essential role of the mucus layer in the decrease of cellular uptake, avoiding potential NPs-cell nuclei interactions. Highlights: A complex in vitro model of intestinal barrier including Caco-2, HT29 and M-cells-like has been constructed. Methodological improvements have been introduced to maintain the highest integrity as a barrier. Changes in the expression of genes related with the main cell functions were monitored. Confocal microscopy has shown to be a powerful tool to follow structural changes in the barrier. This model works well when tested with TiO2 - and SiO2 NPs, widely used in the food industry.